Analysis of the completion of dental records: ethical and legal issues (Research, Society and Development, 2022)
Introduction: Dental records are documents produced daily by dentists and have great administrative and legal value, and should be filled out with utmost care. For this purpose, the filling of dental records produced in the care of patients in the Dentistry course of a private university was analyzed, in view of the ethical and legal issues that guide the filling out of said documentation. Methodology: 350 medical records were analyzed using a form containing questions referring to mandatory data for the correct filling of the main aspects of the medical record. The collected data were analyzed using descriptive statistics using the Statistical Package for Social Sciences – SPSS, version 20.0. Results: Most of the medical records analyzed had all patient identification data. Only 34.9% had the anamnesis completely filled out, 21.4% of the cases had the treatment plan written in full, there were radiographs attached to the medical record in 77.1% of the sample, and 91.1% had the record of full activities. As for the student's signature, it was present in 95.7% of the records, while 93.7% contained the teacher's signature. 4% of the medical records had a copy of the prescription/certificate attached and none of the medical records had the surgical guidelines attached. In 22%, the Free and Informed Consent Form was attached, and only 18.9% of them contained the patient's signature. Conclusion: There is still a lack of attention on the part of students and teachers regarding the care of filling out the medical record, as some of the criteria for a correct filling out were not met.